1T′‐ReS2 Nanosheets In Situ Grown on Carbon Nanotubes as a Highly Efficient Polysulfide Electrocatalyst for Stable Li–S Batteries. Issue 23 (6th May 2020) - He, Jiarui; Bhargav, Amruth; Yaghoobnejad Asl, Hooman; Chen, Yuanfu; Manthiram, Arumugam
Abstract: The practical viability of Li–S cells depends on achieving high electrochemical utilization of sulfur under realistic conditions, such as high sulfur loading and low electrolyte/sulfur (E/S) ratio. Here, metallic 2D 1T′‐ReS2 nanosheets in situ grown on 1D carbon nanotubes (ReS2 @CNT) via a facile hydrothermal reaction are presented to efficiently suppress the "polysulfide shuttle" and promote lithium polysulfide (LiPS) redox reactions. The designed ReS2 @CNT nanoarchitecture with high conductivity and rich nanoporosity not only facilitates electron transfer and ion diffusion, but also possesses abundant active sites providing high catalytic activity for efficient LiPS conversion. Li–S cells fabricated with ReS2 @CNT exhibit high capacity with superior long‐term cyclability with a capacity retention of 71.7% over 1000 cycles even at a high current density of 1C (1675 mA g −1 ). Also, pouch cells fabricated with the ReS2 @CNT/S cathode maintain a low capacity fade rate of 0.22% per cycle. Furthermore, the electrocatalysis mechanism is revealed based on electrochemical studies, theoretical calculations, and in situ Raman spectroscopy. Abstract : A nanocomposite consisting of 2D 1T′‐phase rhenium disulfide (ReS2 ) nanosheets in situ grown onto 1D carbon nanotubes (ReS2 @CNT) with hierarchical architecture is prepared and employed as an electrocatalyst to accelerate the redox reactions in Li–S batteries. Benefiting from several unique advantages, pouch cells fabricated with the ReS2 @CNT/S cathode show outstanding cycling stability with a capacity fade rate of 0.22% per cycle over 130 cycles.